2012
DOI: 10.1248/bpb.b12-00009
|View full text |Cite
|
Sign up to set email alerts
|

Sertindole, a Potent Antagonist at Dopamine D<sub>2</sub> Receptors, Induces Autophagy by Increasing Reactive Oxygen Species in SH-SY5Y Neuroblastoma Cells

Abstract: Autophagy is associated with cell survival and cell death. Autophagy is implicated in the pathophysiology of various human diseases. In order to identify autophagy regulatory molecules, we screened a chemical drug library in SH-SY5Y cells and selected Sertindole as a potent autophagy inducer. Sertindole was developed as an antipsychotic drug for Schizophrenia. Sertindole treatment highly induced the formation of autophagosomes as well as LC3 conversion. Subsequently, Sertindole-induced autophagy was efficientl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 39 publications
4
39
1
Order By: Relevance
“…Recently, an autophagy assay system in SH-SY5Y neuroblastoma cells was built to screen 1120 chemicals and found that first-generation antipsychotics (pimozide, triflupromazine, chlorpromazine, and fluphenazine) and second-generation antipsychotics (such as sertindole) could induce autophagy. It was also discovered that sertindole can cause autophagic cell death in SH-SY5Y neuroblastoma cells [32], which is consistent with our findings in NSCLC cells.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, an autophagy assay system in SH-SY5Y neuroblastoma cells was built to screen 1120 chemicals and found that first-generation antipsychotics (pimozide, triflupromazine, chlorpromazine, and fluphenazine) and second-generation antipsychotics (such as sertindole) could induce autophagy. It was also discovered that sertindole can cause autophagic cell death in SH-SY5Y neuroblastoma cells [32], which is consistent with our findings in NSCLC cells.…”
Section: Discussionsupporting
confidence: 92%
“…However, the mechanism through which this might occur is unclear, and it is conceivable that the differences between individual drugs may reflect the degree to which they may exert such effects [37]. In cell culture studies, a number of antipsychotics have been shown to induce autophagy, a process involved in neurodegenerative processes and cell death [38], suggesting a possible mechanism by which antipsychotics might cause loss of brain volume.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, chlorpromazine, which is a typical antipsychotic agent, induces autophagy by inhibiting the Akt/mTOR pathway [59]. Recently, in vitro studies on the effects of second-generation, atypical antipsychotics demonstrated that sertindole and clozapine are potent autophagy inducers in both neuronal and non-neuronal cell lines [257,261]. Similar to pimozide, clozapine activates the autophagy process via the AMPK–ULK1–Beclin1 pathway, as evidenced by increased levels of autophagy markers (i.e., LC3-II and Atg5–Atg12 conjugate); increased phosphorylation of AMPK and its downstream substrates, namely ULK1 and beclin1; and an increased number of autophagosomes in the frontal cortex in clozapine-treated rats [259].…”
Section: A Step Forward About a Role Of Autophagy In The Pathophysmentioning
confidence: 99%